Penerapan Buku Saku Pada Penyuluhan Sanitasi Higiene Petis Di Home Industri Kampung Lebak Kecamatan Arosbaya - Auliya Hidayatur Rizqi; Lucia Tri Pangesthi; Asrul Bahar; Ila Huda Puspita Dewi (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2024)
This research aims to determine: (1) the activities of instructors and participants in the hygiene sanitation counseling for petis production in the Home Industry of Lebak Hamlet, Arosbaya Village, (2) the effectiveness of the results of hygiene sanitation counseling in the Home Industry of Lebak Hamlet, Arosbaya Village, and (3) the response to the pocketbook from the participants of the hygiene sanitation counseling in the Home Industry of Lebak Hamlet, Arosbaya Village. This study uses a quasi-experimental research design to systematically describe the influence or difference (behavior) between before and after the implementation of hygiene sanitation training in petis production. Research instruments include training assessment sheets, questionnaires, cognitive tests, and documentation, with data analyzed descriptively and using t-tests. The results indicate that the training tools (power point and pocketbook) are overall excellent and suitable for use; 2) The training is proven effective and can enhance the knowledge of food handlers, showing an increased knowledge from food handlers before and after training; 3) Participant responses are very positive, with an average score of 92%.